Harmonisasi Peraturan Equity Crowdfunding pada Aplikasi Santara - Azzahra, Syifa; Hariyani, Iswi; Wahjuni, Edi (PT Matra Cendikia Abadi, 2026)
The development of digital technology has driven a major transformation in the financial sector through financial technology (fintech) innovations, one of which is Equity Crowdfunding (ECF) that serves as a fundraising mechanism for businesses, particularly Micro, Small, and Medium Enterprises (MSMEs). In Indonesia, ECF is regulated under the Financial Services Authority Regulation Number 57 of 2020 and implemented by platforms such as Santara. However, its implementation faces legal challenges due to the lack of alignment with the Capital Market Law, which has not yet accommodated digital securities offerings, resulting in regulatory disharmony and legal uncertainty. This study aims to examine the harmonization of ECF regulations in Indonesia and analyze the legal consequences of ECF practices through the Santara application. The research employs a normative juridical method with statutory and conceptual approaches. The results show that before the enactment of Law No. 4 of 2023 concerning the Development and Strengthening of the Financial Sector, ECF regulations were solely based on the Financial Services Authority Regulation Number 57 of 2020, which holds a lower legal hierarchy than laws, causing regulatory overlap. The enactment of Development and Strengthening of the Financial Sector expands the definition of “securities” to include technology-based instruments and grants legal legitimacy to the Financial Services Authority to regulate and supervise ECF. In the context of Santara’s implementation, regulatory harmonization is crucial to ensure legal certainty, investor protection, and the accountability of platform operators so that crowdfunding activities can be carried out transparently and in accordance with modern capital market principles.